Fibre-metal laminates: A review of reinforcement and formability characteristics. (2020) - Kavitha, K.; Vijayan, R.; Sathishkumar, T.
Abstract: In modern technology development, 50% of air-frame fuselages in aviation sectors, are made up of laminated fibre with metals, for increasing the strength and stiffness to weight ratio. The Fibre-Metal Laminate is the best composites used in aircraft, automobiles and medical fields. Formability of material is the property of deep drawn metal component. In FML(s) the formability depends on the characteristics of metal, nature of fibre, orientation of fibre, bonding nature of metal with fibre. This paper provides an overview of reinforcing metal with fibre, processed in deep drawing and the process parameters to be affected and the defects produced.